PMO-074 A 10 year retrospective review of nasogastric tube use in a district general hospital. (28th May 2012) - Tash, E; Cartwright, A; Steel, L; Subhani, J
Abstract : Introduction: A Nasogastric tube (NGT) is a commonly used device for administration of enteral feeding. It may be used as a bridge to a more definitive procedure (eg, Percutaneous Endoscopic Gastrostomy; PEG) or until patient recovery. The NPSA estimates that " thousands of NGT are placed each day " throughout the UK. 1 However, following a literature review we were unable to find any outcome data for this procedure. Methods: We performed a retrospective review of our nutrition database at Basildon and Thurrock University Hospitals NHS Foundation Trust, that serves a population of 375 000, for all patients who had an NGT inserted between years 2001 and 2011 and analysed the insertion reason and outcome. Results: Over a 10-year period, 2526 patients underwent 2715 episodes of NGT insertions, with a male to female ratio of 49.5% and 50.5%, respectively. The total number of feeding days was 50 584, with a median and mean length of insertion of 10 and 18.7 days, respectively. 189 patients required a repeat NG feeding episode, either within the same or subsequent hospital admission. The referral reasons and outcome data are shown in the Abstract PMO-074 table 1 below. Conclusion: Data analysis revealed that two thirds of all NGT insertions were for patients with dysphagia secondary to a neurological condition, mechanical obstruction or artificial ventilation. Despite these patients being unwell and high risk for complications 46.9% were able to restart oral feeding. However, almost an equal number died while receiving NGT enteral feeding. 2.7% of our cohort were discharged home with some form of long term enteral feeding; either via a PEG or longterm NGT. Competing interests: None declared. Reference: 1. Patient safety alert NPSA/2011/PSA002: reducing the harm caused by misplaced nasogastric feeding tubes in adults, children and infants. 2011. Supporting Information.